Emotional response among architecture students toward virtual biophilic design studio / Shahril Khairi Abdul Shukor - Abdul Shukor, Shahril Khairi (2022)
Design studio as a learning environment plays an important role toward the architecture students' emotions. Students are often exposed to stress and pressure, which lead to exhaustion while completing their projects in the studio. The positive emotions among architecture students should not be neglected and must be a high priority in redefining the design studio as a learning space. Neuroscience studies can help relate emotions and learning, particularly in reducing stress and building up positive emotions among architecture students in their studios. The experiment is conducted to measure the emotional responses towards four different biophilic approaches of indoor wall facades treatment for the design studio using virtual reality as a displayed medium. There are three main instruments used to collect information consist of electroencephalography (EEG) device, heart rate (HR) and galvanic skin response (GSR). This research is based on the data obtained from the experiment results among architecture students from Politeknik Sultan Idris Shah (PSIS).